Analisis Kinerja Pegawai pada Sekretariat DPRD Provinsi Sumatera Utara - Muda Sakti; Isnaini Isnaini; Warjio Warjio (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study is to analyze employee performance and what factors are constraining employee performance at the DPRD Secretariat of North Sumatra Province. The research method used in this research is descriptive with qualitative analysis. Sources of data obtained from interviews, documentation, and observation. With the results of the study that the performance of employees at the Provincial DPRD Secretariat is still relatively poor. Performance indicators according to Benardin's theory that have not worked well are cost-effectiveness (resource effectiveness), namely efforts to avoid wasted materials are still classified as not good, causing wastage at work, such as wasted work equipment and also wasted energy resources. Need for Supervision, namely that employees are not yet able to independently solve problems that arise in work, in the process of carrying out work they are still more dominant in waiting for directions from superiors, so that it can slow down the implementation of community services. While the indicators that are classified as good are quality, quantity, timeliness, and interpersonal impact. The recommendation in this study is that leaders need to determine elements of a more detailed assessment of the elements of performance appraisal. The appraiser needs to eliminate the influence of personal relationships in making an assessment of the performance of subordinates so that the results of the performance appraisal really match the results of the employee's work.